Using a second-person approach to identify disease-specific profiles of social behavior in frontotemporal dementia and Alzheimer's disease. (December 2020) - Visser, Mandy; Wong, Stephanie; Simonetti, Simone; Hazelton, Jessica L.; Devenney, Emma; Ahmed, Rebekah M.; van Langenhove, Tim; Parker, Deborah; Burrell, James R.; Hodges, John R.; Kumfor, Fiona
Abstract: Changes in social behavior are recognized as potential symptoms of behavioral-variant frontotemporal dementia (bvFTD) and semantic dementia (SD), yet objective ways to assess these behaviors in natural social situations are lacking. This study takes a truly social (or second-person) approach and examines changes in real-world social behavior in different dementia syndromes, by analyzing non-scripted social interactions in bvFTD patients ( n = 20) and SD patients ( n = 20), compared to patients with Alzheimer's disease (AD) ( n = 20). Video recordings of 10-min conversations between patients and behavioral neurologists were analyzed for the presence of socially engaging (e.g., nodding, smiling, gesturing) and disengaging behavior (e.g., avoiding eye contact, self-grooming, interrupting). Results demonstrated disease-specific profiles, with bvFTD patients showing less nodding and more looking away than AD, and SD patients showing more gesturing than AD. A principal components analysis revealed the presence of four unobserved components, showing atypical disengaging patterns of behavior. Whole-brain voxel-based morphometry analyses revealed distinct neurobiological bases for each of these components, with the brain regions identified previously associated with behavior selection, abstract mentalization and processing of multi-sensory and socially-relevant information, in mediating socially engaging and disengaging behavior. This study demonstrates the utility of systematic behavioral observation of social interactions in the differential diagnosis of dementia.